Ultrasound-guided tendon debridement improves pain, function and structure in persistent patellar tendinopathy: short term follow-up of a case series. Issue 1 (22nd July 2020) - Masci, Lorenzo; Alfredson, Hakan; Neal, Brad; Wynter Bee, William
Abstract : There is a need for effective therapeutic options for resistant patellar tendinopathy. Ultrasound (US)-guided arthroscopic debridement has demonstrated promising clinical results. Objectives: To prospectively evaluate pain, function, tendon structure and adverse events after US and colour Doppler (CD)-guided arthroscopic debridement for persistent painful patellar tendinopathy. Materials and methods: Twenty-three consecutive patients (19 males and 4 females, mean age 28 years (±8), symptom duration 25 months (±21)), who had failed conservative management including progressive loading, were included. US+CD and ultrasound tissue characterisation (UTC) examination verified the clinical diagnosis and quantified baseline tendon structure. Patients were treated with US+CD-guided arthroscopic debridement followed by a specific rehabilitation protocol. Outcomes were VISA-P score for pain and function and UTC for tendon structure. Adverse events were specifically elicited. Results: At 6-month follow-up, mean VISA-P score increased from 40 (±21.0) to 82 (±15) (mean deviation (MD)=42.0, 95% CI 32 to 53, d =2.4), while organised echo pixels (combined UTC type I+II) increased from 55.0% (±17.0) to 69.0% (±15.0) (MD=14.0, d =0.7, 95% CI 2 to 21). Both outcomes exceeded minimum detectable change values. Twenty-one participants returned to their prediagnosis activity levels, and there were no significant adverse events. Conclusions: US-guided patellar tendon debridement for persistent patellar tendinopathy improved symptoms and tendon structure without complications at 6-month follow-up. A majority (21/23) of the patients returned to their preinjury activity level. Further studies with longer follow-ups, preferably randomised and controlled, are needed.